Community of Macrozoobenthos and Physical-Chemical Parameters in the Watas Hutan Lake, Tanjung Balam Village, Siak Hulu Sub-regency Kampar Regency, Riau Province - Ariska, Tia; Fajri, Nur El; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Watas Hutan Lake is one of the oxbow lakes in the Kampar Regency. In the areas around the lake, there are activities such as oil palm, rubber and banana plantations. To understand the water quality in general, a research was conducted from April to May 2015. This research aims to determine the water quality of the lake based on physical and chemical characteristics and makrozoobenthos community structure. There were three stations, 3 sampling points/ station. Water samples were taken 3 times, once/ week. Parameters measured were abundance, uniformity and dominancy index of the macrozoobenthos and several water quality parameters such as temperature, turbidity, depth, total suspended solid, pH, dissolved oxygen, BOD5, nitrate, phosphate, substrate type, and organic materials. Results shown that there were 12 species (4 classes) of macrozoobenthos, with abundance 353 organisms /m2. There were Oligochaeta (4 species), Insects (3 species), Gastropods (3 species), and Bivalves (2 species). In general, the H' was 2.62-2.82; C was 0.17-0.19 and E was 0.79-0.85. Water quality parameters are as follows : temperature 29-300C, turbidity 4.00-6.30 NTU, depths 1.29-4.03 cm, TSS 4.00-5.30 mg/L, pH 5, dissolved oxygen 2.00-2.73 mg/L, BOD5 5.20-5.50 mg/L, nitrate 0.04-0.06 mg/L and phosphate 0.75-1.14 mg/L. The value of WQI-NSF index of the Watas Hutan Lake was 22.21-24.83, indicates that this river is badly polluted. There was muddy substrate with 39.03-42.20% organic materials content in each area. Based on the values of H’, C and E in the macrozoobenthos community, it can be concluded that the aquatic ecosystem in the Watas Hutan Lake is balance.Keyword: Watas Hutan Lake, Macrozoobenthos, Water quality, WQI-NSF